Evaluation of the intraoperative kinematics during double-bundle anterior cruciate ligament reconstruction using a navigation system - Atsuo Nakamae; Masakazu Ishikawa; Tomoyuki Nakasa; Yasunari Ikuta; Mitsuo Ochi; Nobuo Adachi (Elsevier, 2020)
Background/objective: There is controversy regarding the biomechanical function of the anteromedial (AM) and posterolateral (PL) bundles in isolated tibiofemoral rotation during double-bundle anterior cruciate ligament (ACL) reconstruction. This study aimed to evaluate the biomechanical function of the AM and PL bundles of the ACL using a computer navigation system. Methods: This study involved 15 patients who underwent double-bundle ACL reconstruction. Anteroposterior and isolated rotational knee laxity were measured with a navigation system. The measurements were performed four times, namely, before fixation, after temporary PL bundle fixation, after AM bundle fixation, and after double-bundle reconstruction. With knee flexion ranging from 20° to 60°, we continuously measured the anterior tibial displacement under an anterior drawer stress (100 N using a spring balance). The total range of tibial rotation was also measured under an external and internal rotational torque of 3 Nm. Results: Fixation of either the AM or the PL bundle significantly reduced the anteroposterior displacement at all knee flexion angles. Although the anteroposterior displacement after AM bundle fixation was relatively similar throughout the range of motion (2.4-3.2 mm), the anteroposterior displacement after PL bundle fixation increased continuously with knee flexion (2.2-4.6 mm). With respect to the total range of tibial rotation under external and internal rotational torque, there was no significant difference between AM and PL bundle fixation throughout the range of motion. The total range of tibial rotation was significantly reduced only on double-bundle reconstruction at 20° and 25° knee flexion compared to the pre-reconstruction range (P = 0.015 and 0.036, respectively). Conclusion: The AM and PL bundles function differently for controlling anterior knee laxity throughout the range of motion. The function of the AM and PL bundles was similar for controlling isolated tibiofemoral rotation. Isolated tibiofemoral rotation was significantly controlled only on double-bundle reconstruction at knee flexion angles of 20° and 25°. Keywords: Anterior cruciate ligament, Double-bundle, Navigation system, Intraoperative kinematics, Isolated tibiofemoral rotation